Policy (Institutional) Diversity and Economic Development - Daianu, Daniel (Competitio, 2004)
Diversity, or variety, is the essence of economic life in the sense of underlying choice; economic calculation gives numerical substance to how people make choices in their daily endeavours, either as consumers or entrepreneurs. How does variety/diversity takes shape in the realm of institutions and policy making? Is the range of choices open-ended? The last couple of decades has revealed an overwhelming offensive of the neo-liberal paradigm interms of defining “best practices”. Even language was shaped accordingly with market reforms being seen in a quasi-single theoretical and policy framework. Are we heading towards increasing uniformity with regard to institutional and policy set ups, worldwide? An affirmative answer would underline the successful market based transformation of a series of command economies. Some convergence between institutional patterns in the USA and theEU economies might be alluded to in the same vein A supportive argument for this line of reasoning could be that what matters for individual achievement, in the end, are equal opportunities. But this argument can be turned around when debating the merits of various institutional set ups in terms of creating fair chances for people. A sceptical answer would highlight the mounting challenges which confront societies, whether rich and poor, and the international community in general –in spite of the high hopes of not long ago. The demise of the “New Economy”, the series of corporate scandals in wealthy economies and the subsequent recourse to new regulatory legislation, recurrent financial and currency crises throughout the world, and the controversies surrounding the activity of IFIs, should compel “ideologues”, of all sorts, to be more humble in their prescriptions. This essay argues that there is substantial scope for institutional and policy diversity to operate as a means to foster economic development; that there might be a paradigmatic cycle in the dynamic of economic policies.